Identification of ribonucleotide reductase mutation causing temperature‐sensitivity of herpes simplex virus isolates from whitlow by deep sequencing. Issue 6 (22nd April 2015) - Daikoku, Tohru; Oyama, Yukari; Yajima, Misako; Sekizuka, Tsuyoshi; Kuroda, Makoto; Shimada, Yuka; Takehara, Kazuhiko; Miwa, Naoko; Okuda, Tomoko; Sata, Tetsutaro; Shiraki, Kimiyasu
Key Clinical Message Herpes simplex virus 2 caused a genital ulcer, and a secondary herpetic whitlow appeared during acyclovir therapy. The secondary and recurrent whitlow isolates were acyclovir‐resistant and temperature‐sensitive in contrast to a genital isolate. We identified the ribonucleotide reductase mutation responsible for temperature‐sensitivity by deep‐sequencing analysis.